BEBERAPA FAKTOR YANG BERPENGARUH TERHADAP RESPONS MASYARAKAT BETERNAK SAPI POTONG DI KABUPATEN PARIGI MOUTONG - Rusdin Rusdin (Universitas Tadulako, 2009)
The aim of the research was to identify factors affecting population and productivity of cattle and factors causing people number involved in cattle farming in Parigi-Moutong. The research used descriptive and explorative methods to analyze problems related to those factors affecting the responses of the community on cattle farming system. The results of survey and interview conducted to respondents showed that economic background and land area size were the limiting factors for the cattle farming development. The cattle farming system could not be improved as the main agribussines based on the present condition of the farming system in term of its scale, the farmers’ condition and its main goal. The responses of the community on cattle farming system were also still low particularly for the local people.